Costos de atención y rehabilitación de pacientes con lesiones por accidentes de tránsito en el mundo (2016)
ABSTRACT: To know the direct (dc) and indirect costs (ic) generated by the treatment of patients with moderate or severe injuries caused by traffic accidents (ta) in the world. Methodology: a systematic review of studies assessing the costs of treating victims of traffic accidents older than 16 between 2008 and 2013 was conducted using the PubMed, Embase, Centre for Reviews and Dissemination, Journal Storage and Scielo databases. The quality of the studies was assessed using criteria from Drummond and col, as well as the "Consolidated Health Economic Evaluation Reporting Standards statement (cheers)" and other mechanisms defined by the authors. DCs and ICs were assessed. The burden of disease (bd) was obtained with the disability-adjusted life year (daly), and the quality-adjusted life-year (qaly). The costs generated by disability / rehabilitation and traumatic brain injury (tbi) were analyzed. The monetary costs were expressed in 2010 us dollars (usd) adjusted for inflation. Results: 14 studies were analyzed, 6 of which had a good quality. We found studies with up to 567.000 patients and a duration of 10 years. Direct costs were up to usd 48.082 and indirect costs up to usd 29.706 per patient; the direct costs were exceeded by the indirect costs. The burden of disease showed high variability. In one study, 60% of the patients with severe tbi and 20% with moderate tbi had short term disability; in another study 4.6% of the patients sustained long-term disability. Conclusions: there is great heterogeneity in the cost studies. There is no consensus for assessing the quality of these studies. The indirect costs incurred in traffic accidents are greater than direct costs. The costs of disability and rehabilitation are poorly assessed.